A Peruvian view about clinical pathology services: progress and pending issues - Figueroa-Montes, Luis Edgardo (2020)
Countries do plenty of effort in order to implement the objectives for sustainable development, aiming to achieve universal health coverage. However, access or chances for having high quality Clinical Pathology services are both necessary for supporting medical care systems if such objectives are to be achieved. This access is much more difficult to achieve in low- and medium- income countries. This paper presents an analysis of both the global and local situation in this respect. Four key barriers for delivering high quality and optimal services were identified: insufficient human resources or limited capability of the working force, inadequate education and training, inadequate infrastructure and equipment, and insufficient quality, regulations, and accreditation strategies.